The Effect Of Risk Management On Capital Investment Decisions (Case Studies on Companies at the West Java Chamber of Commerce and Industry and others in Bandung) - R Susanto Hendiarto , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of risk management on capital investment decisions in companies registered with the West Java Chamber of Commerce and Industry in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 112 respondents. The variables studied from each respondent are risk management, capital investment decisions. The type of data collected is primary data. The results showed that risk management had no significant effect on capital investment decisions. The object of this research is that the sample of respondents used is still limited to companies registered with the West Java Chamber of Commerce and Industry in Bandung, therefore further research is needed based on more varied sampling with a longer duration, in order to obtain generalizable results.